2001
DOI: 10.1007/bf02811414
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated molecular evolution of insect orthologues ofERG28/C14orf1: A link with ecdysteroid metabolism?

Abstract: We have analysed the evolution of ERG28/C14orf1, a gene coding for a protein involved in sterol biosynthesis. While primary sequence of the protein is well conserved in all organisms able to synthesize sterols de novo, strong divergence is noticed in insects, which are cholesterol auxotrophs. In spite of this virtual acceleration, our analysis suggests that the insect orthologues are evolving today at rates similar to those of the remaining members of the family. A plausible way to explain this acceleration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…However, further evidence of sequence relatedness was gathered using Psi-BLAST with the yeast sequence against the Metazoa division of Genbank [35]. We included in the iterations the very divergent sequence CG17270 of D. melanogaster , which is the ortholog of ERG28p according to our previous results [23]. This allowed us to detect C14C10.6 as a signinficant hit (S = 120 bits and E = 10 −27 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, further evidence of sequence relatedness was gathered using Psi-BLAST with the yeast sequence against the Metazoa division of Genbank [35]. We included in the iterations the very divergent sequence CG17270 of D. melanogaster , which is the ortholog of ERG28p according to our previous results [23]. This allowed us to detect C14C10.6 as a signinficant hit (S = 120 bits and E = 10 −27 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous paper, given the structural similarity between cholesterol and ecdysteroids, we had proposed that divergent ERGp orthologs might somehow participate in the synthesis of the latter [23]. We have therefore assessed the expressional correlation between candidate genes involved in this process: Dare1 /CG12390 [43], Jhamt [44] and Start1 [45], with dLBR and CG1998 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Erg28p is included in the Hmg2p-induced structures, it could have a direct role on the formation or function of these membrane arrays. Erg28p, like HMGR, is highly conserved and loss of Erg28p results in sterol deficiencies across species (for examples, see Gachotte et al, 2001;Veitia and Hurst, 2001). Last, previous work demonstrated that human testis cells (Veitia et al, 1999) and adrenal cortical cells (Hu et al, 2000) both have increased expression of human Erg28p, as is observed for HMGR (for review, see Federovitch et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Our knowledge of the evolution of enzymes involved in steroid biosynthesis is still fragmentary. Veitia and Hurst (2001) suggested that insects, which are auxotrophs for sterols, would use some of the genes involved in sterol biosynthesis for ecdysteroid biosynthesis, but this hypothesis requires further substantiation. Whether some invertebrates synthesize both vertebrate-type steroids and ecdysteroids is also a challenging question in the field of steroid evolution.…”
Section: Biosynthesismentioning
confidence: 96%